Efficacy of Imatinib in Patients with Platelet-Derived Growth Factor Receptor Alpha–Mutated Gastrointestinal Stromal Tumors - Yoo, Changhoon (Cancer Res Treat, 2016)
PURPOSE: The incidence of gastrointestinal stromal tumors (GISTs) harboring platelet-derived growth factor receptor alpha (PDGFRA) mutations is low, therefore further investigation of the efficacy of imatinib in this subgroup was needed. MATERIALS AND METHODS: Patients with PDGFRA-mutant GISTs who received imatinib as primary therapy for advanced disease between January 2000 and June 2012 were identified from the GIST registry of Asan Medical Center, Seoul, Korea. RESULTS: KIT and PDGFRA genotyping in 823 patients identified 18 patients (2%) with PDGFRA mutations who were treated with first-line imatinib. Exon 18 D842V substitution, non-D842V exon 18 mutations, and exon 12 mutations were detected in nine (50%), four (22%), and five (28%) patients, respectively. Objective response rate differed significantly between patients with the D842V mutation and those with non-D842V mutations (0% [0/5] vs. 71% [5/7], p=0.03). In all patients, median progression-free survival (PFS) and overall survival (OS) was 24.8 months (95% confidence interval [CI], 0.0 to 57.2) and 51.2 months (95% CI, 37.1 to 65.3), respectively. Significantly, poorer PFS was observed for patients with D842V-mutant GISTs than those with non-D842V PDGFRA-mutant GISTs: median 3.8 months (95% CI, 1.4 to 6.3) versus 29.5 months (95% CI, 18.3 to 40.7) (p < 0.001). Patients with the D842V mutation had poorer OS than those with non-D842V PDGFRA mutations: median 25.2 months (95% CI, 12.7 to 37.8) versus 59.8 months (95% CI, 43.0 to 76.5) (p=0.02). CONCLUSION: Imatinib is active against non-D842V PDGFRA-mutant GISTs, whereas GISTs harboring the D842V mutation are primarily resistant to imatinib.